The Influence of Social and Cultural Factors on The Saving Interest of Bank Syariah Indonesia Customers - Azka, Moh. Shadam Taqiyyudin (Journal of Islamic Economic Scholar, 2023)
The aim of this study is to observe the influence of social and cultural factors on the saving interest of customers at Bank Syariah Indonesia in Yogyakarta. The variables in the research include independent variables (social and cultural) and the dependent variable (saving interest). Hypothesis 1 states: There is a significant influence between social (X1) and the saving interest (Y) of Bank Syariah Indonesia's customers in Yogyakarta. Meanwhile, hypothesis 2 states: There is a significant influence between cultural (X2) and the saving interest (Y) of Bank Syariah Indonesia's customers in Yogyakarta. The research object is Bank Syariah Indonesia in Yogyakarta. The research type is causal with a quantitative approach. The population of this study comprises all customers of Bank Syariah Indonesia in Yogyakarta. The research sample consists of 40 users. The sampling technique used a non-probability sampling method employing convenience sampling. Data analysis was conducted using multiple linear regression analysis. The results indicate that cultural factors (X2) significantly influence the saving interest (Y) of Bank Syariah Indonesia's customers, while social factors (X1) do not significantly influence the saving interest (Y) of Bank Syariah Indonesia's customers